The language learning motivation of Chinese postgraduate students in Ireland: From the perspectives of Neo-Confucian learning philosophy - JIANG, RENFENG (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2018)
This doctoral thesis investigates the English language motivation of Chinese students enrolled in one-year Master?s programmes at Trinity College Dublin, in Ireland. These students, from what can be described as a Confucian heritage background, are also taking English for Academic Purposes (EAP) modules at the university in addition to their postgraduate studies. The research examines the language learning motivation of this cohort from a Neo-Confucian perspective depicted in The Great Learning, and explores the validity of a ?Neo-Confucian? motivation construct developed from previous interpretations of Neo-Confucian learning philosophy. The reconceptualised Neo-Confucian motivational construct encompasses the main teachings involved in the Three Objectives and Eight Steps in The Great Learning, which comprises four major components: Self-Cultivation, Self-Improvement, Self-Transformation and Sense of Responsibility. The application of this theory is established on a summary of pertinent Western frameworks as well as an empirical investigation using Western conventional research methods. Therefore, this study can also be seen as an endeavour to bridge Eastern learning values with Western motivational approaches. The research employs mixed and longitudinal approaches to capture the dynamic system in the interaction of the students? motivation, cultural identity and learning context. The design of the empirical study involves three main instruments, namely, participant observation, focus group interviews and a questionnaire. Qualitative data gathered are analysed through two coding cycles with the aid of a computer software, NVivo. Quantitative data collected are processed through descriptive statistics, triangulating the qualitative information captured from observations and interviews. The results of this inquiry indicate a successful application of Neo-Confucian motivational construct in the domain of L2 motivation, which proves that even at the present time, the ancient Eastern philosophical tradition has been yet influential in motivation studies. From the findings, all four motivational components subsumed in the construct were displayed in the participants? learning process. Amongst them, Self-Cultivation and Self-Improvement exerted a major impact on this cohort?s language learning in the non-Confucian heritage context.
APPROVED
Keywords: Neo-Confucian learning philosophy; language learning motivation; self-cultivation; cultural identity